COVID-19 Pandemic: Inequities in Higher Education and Impact on U.S College Students' Failing Mental Health - Katrina E. Pinkney (Journal of Human Services, 2021)
In spring 2020, COVID-19 arrived in the United States and forced the shutdown of nearly all postsecondary institutions. Most college students returned home to participate in virtual learning. For many learners, additional precautions to prevent the spread of COVID-19 and reduce infection rates, including stay-at-home orders, social distancing, and quarantine, reinforced the experience of social isolation. In turn, college students’ mental health deteriorated with the disconnect from formal and informal social supports. Moderate-to-severe anxiety and depression were the most common psychological symptoms. Coping mechanisms included increased substance abuse, social media usage, and reframing of the situation. Most college students did not seek mental health services, even if aware of services on their campuses. Barriers included social stigma, limited access to services, and minimizing of symptoms. Vulnerable populations, for example, racial and ethnic minorities and low income learners, were at even greater risk for poorer mental health outcomes due to additional social and economic factors. Sometimes, too, inequitable practices at colleges and universities hindered the stability and betterment of students’ mental wellbeing. In response, recommendations are provided for college administration to promote diversity, equity, and inclusion.